2003
DOI: 10.1063/1.1531651
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectroscopic Database on Acetylene, X̃ 1Σg+ (12C2H2, C212D2, and C213H2)

Abstract: Information on the vibrational energy states in acetylene (12C2H2, C212D2, and C213H2) is gathered: spectroscopic constants (vibrational frequencies and anharmonicities, vibration-rotation interaction parameters), observed vibrational energy states and complete sets of predicted vibrational energies and predicted principal rotational constants Bv for states of C212H2, C212D2, and C213H2 up to 15000, 10000, and 12000 cm−1, respectively. Statistical parameters (partition functions and integrated number of states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 1 publication
3
149
1
Order By: Relevance
“…From the experimental results, there are excellent agreements of the bond length of normal acetylene with previous literature studies. For instance, in recent research by Herman et al, 11 bond length of C-H and C-C in C 2 H 2 have been reported as 105.756(52) pm and 120.830 (20) pm respectively. While in this study we found the C-H and C-C bond length as 1.08653±0.0057 Å and 1.18983±0.0010 Å respectively.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…From the experimental results, there are excellent agreements of the bond length of normal acetylene with previous literature studies. For instance, in recent research by Herman et al, 11 bond length of C-H and C-C in C 2 H 2 have been reported as 105.756(52) pm and 120.830 (20) pm respectively. While in this study we found the C-H and C-C bond length as 1.08653±0.0057 Å and 1.18983±0.0010 Å respectively.…”
Section: Resultsmentioning
confidence: 96%
“…The infra-red spectroscopy has been widely utilized for probing the vibrational and rotational energy levels of molecules by chemists for structural elucidations. The vibrationalrotational spectra of acetylene molecule both in the ground electronic and excited states in the last decades were extensively investigated using spectroscopic methods [10][11][12] . The annex 1 of Herman et al, 10 provides an abundant reference of most literature papers of the spectroscopic data on acetylene in the ground electronic state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometry optimisations carried out for the complex and isolated C 2 H 2 with basis set sizes up to sextuple zeta quality show that complexation with He changes the geometry of C 2 H 2 at most by 0.0001Å. The C 2 H 2 unit was consequently fixed at its experimental ground state expectation geometry, 88 r 0 (CC) = 1.20830Å and r 0 (CH) = 1.05756Å.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…4 corresponds to particular frequency contributions of C 2 H 2 to the rotational wavepackets. The observed lines were recorded at a pump laser intensity of 2.5×10 11 Wcm −2 and coincide with the beat frequencies of free C 2 H 2 at 6b + 4nb, where b is the C 2 H 2 rotational constant † (b = 1.1767 cm −1 ) 88 and n = 0, 1, 2, 3. The first line at 6b frequency is equivalent to the J ′ = 2 ← J ′′ = 0 transition, with successive lines at 10b, 14b, 18b.…”
Section: Time-resolved Alignment and Fourier Transformationmentioning
confidence: 99%